An analytical model to evaluate the cocktail party effect in restaurant dining rooms: A case study. (15th December 2015) - Leccese, Francesco; Tuoni, Giuseppe; Salvadori, Giacomo; Rocca, Michele
Highlights: This study aims to propose a model to evaluate acoustic conditions in dining rooms. A simplified analytical model has been used to evaluate the cocktail party effect. The authors have analysed a case study of a dining room of a restaurants in Italy. The results have been compared with those obtained from acoustic simulation software. Whit the use of acoustic panels, different room corrections have been proposed. Abstract: This paper proposes the use of a simplified analytical model to evaluate acoustic conditions in restaurant dining rooms required for ensuring the intelligibility of conversations. The model is useful for design applications and is suitable for evaluating the maximum number of speakers present in a restaurant room in order to ensure intelligibility of conversations taking place at each table in the presence of background noise caused by conversations at other tables. The maximum number of speakers is studied in relation to the sound level difference between useful and disturbing sound, sound absorption of the room, and the average speaker–listener distance. The model is applied to the case of a dining hall in a multipurpose centre, which is currently in the planning stage.